2003
DOI: 10.1044/1058-0360(2003/080)
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Standardized Measures of Language and Measures of Spontaneous Speech in Children With Autism

Abstract: This study investigated the relationship between scores on standardized tests (Clinical Evaluation of Language Fundamentals [CELF], Peabody Picture Vocabulary Test-Third Edition [PPVT-III], and Expressive Vocabulary Test) and measures of spontaneous speech (mean length of utterance [MLU], Index of Productive Syntax, and number of different word roots [NDWR]) derived from natural language samples obtained from 44 children with autism between the ages of 4 and 14 years old. The children with autism were impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
126
0
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(146 citation statements)
references
References 35 publications
10
126
0
10
Order By: Relevance
“…Previous research (Condouris et al, 2003;Huang et al, 1997;Tyler & Tolbert, 2002) suggests that analyzing a child's language should be completed both standardly and naturally. The present study adds to the literature by extending the results to the evaluation of morphosyntactic components of language specifically.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research (Condouris et al, 2003;Huang et al, 1997;Tyler & Tolbert, 2002) suggests that analyzing a child's language should be completed both standardly and naturally. The present study adds to the literature by extending the results to the evaluation of morphosyntactic components of language specifically.…”
Section: Resultsmentioning
confidence: 99%
“…Spontaneous language samples can be collected using conversation, free play, story generation, and interviews (Evans & Craig, 1992;Southwood & Russell, 2004). Contrary to naturalized assessments, standardized assessments follow a systematic structure (Condouris et al, 2003). Brown (1973) provided a significant source of research for naturalized assessment by studying child language development through the transcription and analysis of spontaneous speech in a longitudinal study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rollins and Snow (16) suggested that, apparently, pragmatic abilities of autistic children contribute to their grammatical acquisition. Other authors (7,17) observed that autistic children present lexical syntactic and grammatical handicaps in standard tests and spontaneous speech. Recent researches investigated the relations between pragmatic and grammatical development (18) and between grammatical development and syntax (8,14,(19)(20).…”
Section: Introductionmentioning
confidence: 94%
“…These samples may provide important information about their social-linguistic functioning, especially when variables such as context, familiarity and cognitive demands are controlled. Besides, this kind of data reflects the language use productivity (6)(7).…”
Section: Introductionmentioning
confidence: 99%